2016
DOI: 10.1016/j.jde.2016.04.026
|View full text |Cite
|
Sign up to set email alerts
|

Non-smooth saddle-node bifurcations III: Strange attractors in continuous time

Abstract: Non-smooth saddle-node bifurcations give rise to minimal sets of interesting geometry built of so-called strange non-chaotic attractors. We show that certain families of quasiperiodically driven logistic differential equations undergo a non-smooth bifurcation. By a previous result on the occurrence of non-smooth bifurcations in forced discrete time dynamical systems, this yields that within the class of families of quasiperiodically driven differential equations, non-smooth saddle-node bifurcations occur in a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 40 publications
(44 reference statements)
0
18
0
Order By: Relevance
“…The bifurcation occurs when the set of bounded solutions is empty at one side of a certain value of the parameter and contains a classical attractor-repeller pair on the other side. Detailed descriptions of this situation for some cases of nonautonomous quadratic differential equations are given in [20] and [13], where the possibility of occurrence of strange nonchaotic attractors is carefully analyzed.…”
Section: One-parametric Variation Of the Global Dynamics Let Us Now Consider The One-parametric Family Of Equationsmentioning
confidence: 99%
“…The bifurcation occurs when the set of bounded solutions is empty at one side of a certain value of the parameter and contains a classical attractor-repeller pair on the other side. Detailed descriptions of this situation for some cases of nonautonomous quadratic differential equations are given in [20] and [13], where the possibility of occurrence of strange nonchaotic attractors is carefully analyzed.…”
Section: One-parametric Variation Of the Global Dynamics Let Us Now Consider The One-parametric Family Of Equationsmentioning
confidence: 99%
“…In addition, the simulations in Figures 2(b) and Figure 4(e)-(h) provide similar numerical evidence for the existence of nonsmooth bifurcations in the qpf Allee model (2) and (3) below. These findings are backed up by rigorous results in [Fuh14,Fuh16], showing that non-smooth fold bifurcations occur for open sets of parameter families of quasiperiodically forced scalar ODE's. They can therefore be robust and persistant under small perturbations of the system.…”
Section: Introductionmentioning
confidence: 77%
“…(19) In fact, (19) a priori only yields a local flow where trajectories may diverge and hence not be defined for all times t ∈ R. As we will only deal with bounded solutions (see also Lemma 4.5), this issue is not of further importance. We refer the interested reader to [Fuh16] for more details. Now, in order to apply the above statements to flows defined by equations of the form (19), it is crucial that the validity of the assumptions can be read off directly from the differential equations.…”
Section: Preliminariesmentioning
confidence: 99%
See 1 more Smart Citation
“…The choice of each one of these categories defines a different research line, and all of them have shown their relevance. The works of Braaksma et al [9], Alonso and Obaya [2], Johnson and Mantellini [24], Fabbri et al [14], Langa et al [29,30], Rasmussen [43,44], Núñez and Obaya [37], Pötzsche [41,42], Anagnostopoulou and Jäger [3], Fuhrmann [16], and Caraballo et al [12], develop some of these lines, providing nonautonomous transcritical, saddle-node and pitchfork bifurcation patterns. In some cases these nonautonomous phenomena admit a dynamical description analogous to that of the autonomous case.…”
Section: Introductionmentioning
confidence: 99%